2016
DOI: 10.1080/02626667.2016.1217415
|View full text |Cite
|
Sign up to set email alerts
|

Impact of precipitation and temperature changes on hydrological responses of small-scale catchments in the Ethiopian Highlands

Abstract: Hydrological response of catchments with different rainfall patterns was assessed to understand the availability of blue and green water and the impacts of changing precipitation and temperature in the Ethiopian Highlands. Monthly discharge of three small-scale catchments was simulated, calibrated, and validated with a dataset of more than 30 years. Different temperature and precipitation scenarios were used to compare the hydrological responses in all three catchments. Results indicate that runoff reacts disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 58 publications
(74 reference statements)
4
4
0
1
Order By: Relevance
“…Manifestations about hydrological components of the different types of climate change were related to the response relationship. In one case, the effects of precipitation and temperature changes on hydrological components might be consistent with each other which was same as Lemann's opinions [37]. Such as when the climate change type (I) occurred, the GWF would increase, whereas in type (II), the decrease of precipitation and DTR commonly promoted the decrease of GWF.…”
Section: Discussionsupporting
confidence: 71%
“…Manifestations about hydrological components of the different types of climate change were related to the response relationship. In one case, the effects of precipitation and temperature changes on hydrological components might be consistent with each other which was same as Lemann's opinions [37]. Such as when the climate change type (I) occurred, the GWF would increase, whereas in type (II), the decrease of precipitation and DTR commonly promoted the decrease of GWF.…”
Section: Discussionsupporting
confidence: 71%
“…The correlation (r = 0.54) is shown in Figure 6 (left), with the mean annual precipitation and drainage ratio data from the 323 watersheds in the upper Blue Nile basin. This correlation was already observed by Lemann et al [30] in a comparison of the different hydrological responses of three small-scale catchments in the upper Blue Nile basin; after a predefined amount of precipitation, additional rainfall apparently increases the share of blue water leaving a catchment. Liu et al [78] and Steenhuis et al [79] discussed an effective precipitation threshold (precipitation minus potential evaporation) of 500 mm, where hydrological response can be predicted by its linear relationship to precipitation.…”
Section: Spatial Variabilities In Drainage Ratiosupporting
confidence: 75%
“…More detailed discharge modelling was conducted by many studies at the catchment level in different watersheds in the upper Blue Nile basin [22][23][24][25][26][27][28][29]. Lemann et al [30] showed the different hydrological responses to different rainfall patterns and different meteorological conditions in the upper Blue Nile basin, but only at the sub-basin level. Prior to this study, there was no detailed analysis of hydrological responses and discharge simulations over a longer time period at the national basin level, with a soil and land use map of a high spatial resolution and DEM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Northern Lake Erie Basin in Canada (Zhang et al 2018). The evapotranspiration was expected to increase at rates similar to those of the temperature and rainfall dynamics, which is in agreement with findings (Gebre and Ludwig 2015;Lemann et al 2017;Teklesadik et al 2017;Birhan and Worku 2018) in the Upper Blue Nile Basin. The evapotranspiration, however, is expected to decrease during winter under RCP8.5, contrary to most of the studies conducted in the surrounding watersheds (Enyew et al 2014;Ayele et al 2016).…”
Section: Discussionsupporting
confidence: 90%